Strategic landfill site selection for sustainable waste management in Phu Yen Province, Vietnam using geospatial technologies - Diem-My Thi Nguyen; Dorian Tosi Robinson; Christian Zurbrügg; Thi Hanh Tien Nguyen; Huu-Lieu Dang; Van-Manh Pham (Ecological Informatics)
Solid waste management is a growing global challenge, especially in developing countries such as Vietnam, where rapid urbanisation and inadequate infrastructure intensify environmental and public health risks. Landfilling is one of the most environmentally harmful waste disposal methods. However, it remains widely used in many countries because of its cost-effectiveness. Proper disposal of solid waste is a significant priority for reducing environmental pollution. Selecting suitable landfill sites requires consideration not only of physical and environmental aspects but also of economic and social factors. In Phu Yen Province, located in south central Vietnam, solid waste management faces growing challenges in solid waste management. Limited landfill infrastructure and poor operational standards are already impacting public health and the environment. Moreover, with existing landfills approaching the end of their usable lifespans, identifying new, appropriate sites has become an urgent priority. This study introduces a novel approach that integrates a geographic information system (GIS)-based multi-criteria decision analysis (MCDA) with a fuzzy analytic hierarchy process (Fuzzy AHP) to enhance landfill site suitability assessments. This study's approach enables a holistic evaluation of economic, environmental, topographical, and social factors, thereby ensuring a more comprehensive decision-making process. The findings reveal that 45 % of the study area is very highly or highly potential for landfill sites, 28 % is of medium potential, 27 % is of low or very low potential, and 25.7 % of the existing landfill locations pose significant environmental and human health risks. A spatial distribution map obtained from a comprehensive analysis incorporating economic, social, environmental, and topographical factors helped identify potential future sites for solid waste disposal in Phu Yen Province. The methodology demonstrated in this study is highly transferable and can be applied to other low- and middle-income countries that face similar waste management challenges.